A Design of Adaptive Quantizer for MPEG-2 Video Coding - 孙军; 张文军; 余松煜 (Tongxin xuebao)
Based upon studying the strategy for adaptive quantization suggested by MPEG-2 Test Model 5,a new quantizer is presented in this paper.Block-based visual activities are analyzed to exploit local perceptual characteristics in the macroblock.In order to decide the adaptive perceptual quantization factor,macroblock characteristic is identified by evaluating comprehensively each block’s local activity within this macroblock.Experiment results show that coding distortion is uniformly distributed across the image with the proposed quantizer ,and picture quality is improved. In particular,block artifacts in flat area and distortion at edges on flat backgrounds are significantly reduced.